Kidney and Pancreas Transplantation A Practical Guide - Srinivas, T. R.; Shoskes, Daniel A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2011)
The transplant physicians and surgeons at Cleveland Clinic have collaborated to produce, Kidney and Pancreas Transplantation: A Practical Guide. This volume is devoted to kidney and pancreas transplantation and is well grounded in scientific principles, quantitative clinical reasoning, clinical pharmacology, tested clinical practices and overall clinical applicability. Also addressed are key aspects in the initiation, maintenance and sustained growth of viable clinical programs in kidney and pancreas transplantation. Kidney and Pancreas Transplantation: A Practical Guide will be of great value to transplant physicians as well as medical and surgical fellows who intend to pursue an interest in transplantation.
Chapter 1: The Immune Response to Transplanted Organs -- Chapter 2: The Histocompatibility Laboratory In Clinical Transplantation -- Chapter 3: Immunosuppressive Therapy In Kidney And Pancreas Transplantation -- Chapter 4: Clinical Pharmacologic Principles and Immunosuppression -- Chapter 5: Pathology of Kidney and Pancreas Transplantation -- Chapter 6: Design, Conduct, and Report of Clinical Trials of Immunosuppressive Regimens in Solid Organ Transplantation -- Chapter 7: Outcomes of Kidney and Pancreas Transplantation -- Chapter 8: Medical And Surgical Evaluation Of The Adult Kidney Transplant Candidate -- Chapter 9: Selection and Preparation of the Pancreas Transplant Recipient -- Chapter 10: Kidney Transplant Recipient Surgery -- Chapter 11: Issues and Surgical Techniques to Expand the Pool of Kidneys Available for Transplantation -- Chapter 12: Pancreas Transplantation: Surgical Techniques -- Chapter 13: Laparoscopic Living Kidney Donation -- Chapter 14: Perioperative and Anesthetic Management in Kidney and Pancreas Transplantation Management -- Chapter 15: Surgical Complications After Kidney Transplantation -- Chapter 16: Urological Complications after Kidney Transplantation -- Chapter 17: Medical Management of Kidney Transplant Recipients -- Chapter 18: Infectious Complications: Prevention and Management -- Chapter 19: Living Kidney Donation: Pre- and Post-Donation Evaluation and Management -- Chapter 20: Psychology, Quality of Life and Rehabilitation after Kidney and Pancreas Transplantation -- Chapter 21: Kidney Allocation System for Deceased Donor Kidneys in the United States -- Chapter 22: Ethics of Transplantation -- Chapter 23: Long-Term (20-40 Years) Renal Transplant Outcomes -- Chapter 24: Quantitative Aspects of Clinical Reasoning: Measuring Endpoints and Performance -- Chapter 25: The Business of Transplantation.
Keywords: Medicine; Surgery; Abdomen -- Surgery; Transplantation of organs, tissues, etc; Urology; Medicine & Public Health; Urology/Andrology.; Transplant Surgery; Abdominal Surgery; Surgery